The Russo-Turkish Agreement of January 26, 1914 in the Pages of Constantinople Armenian Periodicals - Hovsepyan, Mariam (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
The Russo-Turkish Agreement signed on January 26, 1914, did not resolve the Armenian Question. The Ottoman authorities invalidated it, thereby preventing the European inspectors N. Hoff and L. Westenenk from commencing the activities stipulated by the document. This course of action was officially justified by the fact that World War I had begun on July 19, 1914, and under wartime conditions, there was no longer a need to implement the agreement. These realities were reflected in the Armenian press published in Constantinople. In particular, the widely circulated daily newspapers Azatamart and Zhamanak actively covered this issue. They also presented to their readers the expectations and hopes of Armenians regarding the agreement. Opinions varied. Many believed that under the general supervision of the Russian Empire, the agreement would finally safeguard the long-violated rights of Armenians. A significant segment of Armenian society, however, remained skeptical, recalling a number of previously adopted decisions and documents that had in no way contributed to a pro-Armenian resolution of the Armenian Question. Azatamart called upon everyone to remain realistic, while Zhamanak urged patience and waiting for further developments. Alongside expressing their own positions, these periodicals also addressed the viewpoints of pro-European and pro-Russian groups. Analytical articles conclued that, overall, Western Armenians aspired to live a peaceful and secure life in their ancestral homeland. It was noted that although the agreement envisaged reforms in Armenian-populated provinces, the Ottoman government had for decades merely spoken of implementing reforms across the empire, in practice leaving such programs confined to paper.
Keywords: History; Armenian periodicals; Constantinople